The 21st-century skills scales: many facet Rasch measurements - Ma'rifatin Indah Kholili; Adi Dewantoro; Naharus Surur; Novita Tri Hapsari (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aims to develop a 21st century skills scale for prospective school counselor. The method used is the research and development. The data were analyzed using content analysis/expert judgment with many-facet Rasch model (MFRM). Three facets were employed: scale, item, and measurement criteria. The initial version of the scale comprises 129 items measuring four aspects: way of thinking, way of working, tools for working, and living in the world. However, 78 items were deemed valid following the expert judgment analysis result. The inter-rater agreement opportunity shows raters’ similarity score of 10,836, implying that experts in this study tend to give similar assessments. This research results in a 21st century skills scale for prospective school counselors with a total of 78 valid items. The purpose of this study was to develop a 21st century skills scale for prospective school counselors that had been fulfilled, the instrument had been tested for validity and reliability based on expert judgment. The current research recommends that further research be carried out to develop a 21st century skills scale instrument for prospective educators in other scientific fields.